2006
DOI: 10.1891/jcop.20.3.327
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness: A Primrose Path for Therapists Using Manualized Treatments?

Abstract: During the past 2 decades, the popularity of mindfulness as a desirable patient characteristic has increased considerably. Described as the tendency to be attentive to and aware of what is occurring in the moment, mindfulness is incorporated into several established therapeutic techniques, with some impressive outcome data. To our knowledge, there have been no treatment studies investigating the effect of therapist mindfulness on therapy outcome. The current study examined the relation between therapist mindfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 19 publications
(23 reference statements)
0
22
0
2
Order By: Relevance
“…In sum, therapist mindfulness was a significant predictor of clients' global functioning at termination, and the relationship between mindfulness and outcome was negative. Stanley et al (2006) conclude that none of the analyses they conducted gave support to the idea that higher levels of therapist mindfulness contribute to better therapeutic outcomes when manualized treatments are used. Stratton (2006) designed a study to evaluate the relationship between trait-level therapist mindfulness and treatment outcomes, as well.…”
Section: Health Care Providers and Treatment Outcomesmentioning
confidence: 90%
See 2 more Smart Citations
“…In sum, therapist mindfulness was a significant predictor of clients' global functioning at termination, and the relationship between mindfulness and outcome was negative. Stanley et al (2006) conclude that none of the analyses they conducted gave support to the idea that higher levels of therapist mindfulness contribute to better therapeutic outcomes when manualized treatments are used. Stratton (2006) designed a study to evaluate the relationship between trait-level therapist mindfulness and treatment outcomes, as well.…”
Section: Health Care Providers and Treatment Outcomesmentioning
confidence: 90%
“…Therapists' mindfulness was measured, as was clients' symptom severity, symptom improvement, and overall functioning. None of the analyses conducted by Stanley et al (2006) showed support for the role of therapist mindfulness as a significant predictor of positive treatment outcomes. In fact, greater therapist mindfulness was associated with worse treatment outcome.…”
Section: Health Care Providers and Treatment Outcomesmentioning
confidence: 91%
See 1 more Smart Citation
“…Enquanto "posturas", serão constituintes da "consciência da experiência". Neste sentido, os terapeutas que são tendencialmente mindful nas suas vidas pessoais (o que, nessa circunstância, determina a característica como "traço", parte do self do terapeuta), poderão estar menos mindful enquanto terapeutas (Stanley et al, 2006)…”
Section: Mindfulness E Psychological Mindedness: Variáveis Da Consciêunclassified
“…A potencial utilidade da prática pessoal de mindfulness para terapeutas é uma qualidade terapêutica desejável, quer a nível pessoal, quer a nível profissional (Hick, 2008;Dryden & Still, 2006;Stanley et al, 2006). Germer (2005) defende que a mindfulness pode "tornar-se um constructo que aproxima a teoria clínica, a investigação e a prática, e ajuda a integrar as vidas pessoal e profissional dos terapeutas" (p. 11).…”
Section: Conclusõesunclassified